A review of chemical constituents, traditional and modern pharmacology of fig (Ficus carica L.), a super fruit with medical astonishing characteristics - Hesam Shahrajabian, Mohamad; Sun, Wenli; Cheng, Qi (Polish Journal of Agronomy, 2021)
Fig (Ficus carica L.) belongs to Moraceae family, is clearly of greatest importance as a source of human food and nutrition. The fig’s fruits are a good natural source of nutrients, phytochemicals, and minerals which may improve human health and nutrition. All relevant papers in English language were collected. The keywords of pharmacology, traditional medicine, phytochemistry, fig and health promoting were searched in Google Scholar, Scopus, Research Gate and PubMed. The most important pharmacological characteristics of Ficus carica are anticancer, antioxidant, antiparasitic, antiviral, antibacterial, antimutagene, anti-inflammatory, anti-angiogenic, antidiabetic, antipyretic, reproductive, antiplatelet, endocrine, immunological, dermatological, antispasmodic, hypolipidemic, nootropic, antidiarrheal, nephro- and hepato-protective and anti-warts effects. Fruits have anti-oxidative, anti-spasmodic and nephroactivity protective, branches have both anti-oxidant and anti-inflammatory characteristics. Leaves have anti-inflammatory, anti-pyretic, anti-diabetic, helpato-protective, anti-angiogenic, immunomodulatory, antinematicidal effect, inhibit of osteoclastogenesis, and are used in the case of ischemia and reperfusion injuries. Latex has anti-cancer, anti-bacterial, anti-angiogenic, antiviral and anthelmintic properties. Moreover, fig’s stem bark has anti-diabetic characteristics. The aim of this review was to go through some important studies on chemical constituents and pharmacological effects of fig. The obtained findings show potential of different parts of the fig plant as an additive in the food and pharmaceutical industries.